Pengeringan biji jagung menggunakan pengkondisi udara - Mulyanto, A.; Mirmanto, M.; Susana, I.G.B.; Alit, I.B.; Nuarsa, I.M. (Dinamika Teknik Mesin, 2019)
This study aims to determine the effect of air velocity on the rate of drying corn. Corn seeds were placed after the evaporator of an air conditioner, so that the air came out of the evaporator entered the drying chamber. The water in the corn was evaporated and sucked by dry cold air and then it was condensed in the evaporator. The results show that the mass of corn seeds decreases with the time; the drying rate also decreases with the time and mass-based drying rates at low air speeds are faster than at high air speed. The air conditioner can be used for drying seeds.